Bridging Perceived and Actual Organizational Performance: The Role of Entrepreneurial Leadership - Eni Cahyani; Asri Laksmi Riani; Mugi Harsono; Joko Suyono; Usman Magaji Abdullahi (Jurnal Ilmu Manajemen, 2025)
To isolate PTS performance to see how these factors directly affect the perception of overall organizational performance, in addition to seeing whether organizational performance with the perception of organizational performance can be strengthened by entrepreneurial leadership. This study used an online descriptive survey, with a questionnaire as a data collection instrument. 416 participants took part in this study. Respondents were selected through snowball sampling. Data were analyzed using SEM-PLS analysis. Organizational performance has a positive and significant effect on the perception of organizational performance, while the role of entrepreneurial leadership is successful as a moderator of entrepreneurial leadership but weakens the relationship between PTS performance on perception of the performance. The study shows that public sector organizations have a positive image in terms of performance aspects related to PTS productivity, entrepreneurial leadership successfully moderates organizational performance with perceptions of organizational performance.  This is also possible due to the inconsistency PTS strategy. Unique The study has developed performance variables that are generally used as exogenous variables to see stakeholder perceptions.